The Cult Statues of the Pantheon. (22nd June 2017) - Thomas, Edmund
ABSTRACT: This article reconsiders the possible statuary of the Pantheon in Rome, both in its original Augustan form and in its later phases. It argues that the so-called 'Algiers Relief' has wrongly been connected with the Temple of Mars Ultor and is in fact evidence of the association of the Divus Julius with Mars and Venus in the Pantheon of Agrippa, a juxtaposition which reflects the direction of Augustan ideology in the 20sb.c. and the building's celestial purpose. This triple statue group became the focus of the later Pantheon, and its importance is highlighted by the hierarchized system of architectural ornament of the present building.